Radical Hospitality : From Thought to Action - Kearney, Richard (Book collections on Project MUSE., 2021)
Radical Hospitality addresses a timely and challenging subject for contemporary philosophy: the ethical responsibility of opening borders, psychic and physical, to the stranger. The book engages urgent moral conversations concerning identity, nationality, immigration, peace, and justice for the work of living together.